DEVELOPING INTERCULTURAL COMMUNICATION COMPETENCE IN TEACHING ENGLISH - Nurmamatova Umida Akmal kizi (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
This article explores various methods used in learning and developing foreign languages. While learning a language, one often encounters challenges, but primarily, these challenges are clearly reflected in the culture associated with the language. This is because external appearance often reflects national identity. At the same time, learning a language means delving into the heart of different nations and understanding their essence, since no language can truly be learned without feeling it.